Green Marketing's Role in Molding Customer Buying Decision for Green Products - Chaudhary, Manoj Kumar; Chaudhary, Rajesh Kumar; Pokharel, Pramila (Journal of Emerging Management Studies, 2024)
Purpose – The purpose of the study is to investigate how customer purchase decisions are impacted by green marketing. It specifically looks at how important elements like environmental awareness, eco-labeling, eco-friendly packaging, eco-advertising, and sustainable pricing impact customers' propensity to buy eco-friendly goods. By examining these components, the study attempts to provide insightful information on how these components influence consumers' opinions about environmentally friendly goods.Design/methodology/approach – The research adopted a quantitative approach based on the survey conducted among 341 customers of green products. A structured questionnaire featuring 5-point Likert scale items were used to collect the first-hand data. The collected raw data were processed through MS-Excel and SPSS. Descriptive statistics, correlation, and regression analysis have been used to analyze the data and validate the generated hypothesis.Findings and Conclusion – Regression analysis revealed that customers' decisions to buy green products are noticeably affected by green marketing. Environmental awareness, eco-labeling, green pricing, and green packaging are the important variables that have a significant impact on consumer purchasing decisions. The study indicates that green marketing has a critical role in shaping consumer preferences because of the increasing demand for eco-friendly products. Therefore, firms in Nepal can improve profitability and competitiveness while also helping to preserve the environment when sustainable practices successfully combine with green marketing techniques.Implications – Companies producing green products can use the study's findings to improve their green marketing strategies by emphasizing on green marketing tools. Customers are becoming more aware of green certifications and ingredients; therefore, transparency is essential to preventing greenwashing.  Offering true sustainable products with solid environmental claims should be a top priority for businesses. Government regulations need to encourage companies to use sustainable practices and promote the preservation of the environment. This study highlights the mutual obligation of businesses and customers to save the environment, while also offering managers an outline for boosting reputation, profitability, and competitiveness.